Climate Controls on River Chemistry - Li, Li; Stewart, Bryn; Zhi, Wei; Sadayappan, Kayalvizhi; Ramesh, Shreya; Kerins, Devon; Sterle, Gary; Harpold, Adrian; Perdrial, Julia (Earth's future, 2022)
How does climate control river chemistry? Existing literature has examined extensively the response of river chemistry to short‐term weather conditions from event to seasonal scales. Patterns and drivers of long‐term, baseline river chemistry have remained poorly understood. Here we compile and analyze chemistry data from 506 minimally impacted rivers (412,801 data points) in the contiguous United States (CAMELS‐Chem) to identify patterns and drivers of river chemistry. Despite distinct sources and diverse reaction characteristics, a universal pattern emerges for 16 major solutes at the continental scale. Their long‐term mean concentrations (Cm) decrease with mean discharge (Qm), with elevated concentrations in arid climates and lower concentrations in humid climates, indicating overwhelming regulation by climate compared to local Critical Zone characteristics such as lithology and topography. To understand the CmQm pattern, a parsimonious watershed reactor model was solved by bringing together hydrology (storage–discharge relationship) and biogeochemical reaction theories from traditionally separate disciplines. The derivation of long‐term, steady state solutions lead to a power law form of CmQm relationships. The model illuminates two competing processes that determine mean solute concentrations: solute production by subsurface biogeochemical and chemical weathering reactions, and solute export (or removal) by mean discharge, the water flushing capacity dictated by climate and vegetation. In other words, watersheds function primarily as reactors that produce and accumulate solutes in arid climates, and as transporters that export solutes in humid climates. With space‐for‐time substitution, these results indicate that in places where river discharge dwindles in a warming climate, solute concentrations will elevate even without human perturbation, threatening water quality and aquatic ecosystems. Water quality deterioration therefore should be considered in the global calculation of future climate risks. Key Points Continental‐scale river chemistry data show that mean discharge predominantly regulates mean concentrations of 16 solutes A simple watershed hydro‐biogeochemical reactor model illuminates that river chemistry is driven by the relative rates of solute addition (by reactions and input) and solute export Where river discharge dwindles in a warmer climate, higher concentrations will deteriorate water quality even without human perturbations